Optimalisasi Taman Baca Masyarakat (TBM) Melalui Trisentra: (Sentra Baca, Sentra Bimbel Dan Sentra Kriya) - Siti Maesaroh, Tasbiah; Khofifah, Hafsoh; Nur Sopiyah, Imas; Rahmat Pramudia, Joni (E-Coops-Day, 2025)
The reading interest of the Indonesian people is very concerning, namely only 0.001% which means only one in 1,000 people are diligent in reading, and this puts Indonesia in 62nd position out of 70 countries in reading interest. Low interest in reading is caused by several factors, 1). Interest in reading is not instilled from an early age, 2) educational facilities are not evenly distributed and 3) lack of book production, especially in the regions. The implementation method is taken through three stages, namely the planning stage in which there is an observation and need assessment stage for the community and compiling the RPP, the second is the implementation stage, and the third is the evaluation stage, this evaluation is carried out in process evaluation or result evaluation. Evaluation of this process includes evaluation of the implementation of program activities starting from the planning stage to the evaluation stage. Optimization of Community Reading Parks (TBM) Through Trisentra (Reading Centers, Bimbel Centers and Craft Centers) produces learning experiences for students in preparing young people in Pasir Handap Village to face educational challenges in the future.